PROFILE OF MISCONCEPTION ON GENETIC SUBSTANCE TOPIC ON STUDENT GRADE XII WITH FOUR-TIER DIAGNOSTIC TEST - Syamsiar, Ais Agustining; Raharjo, Raharjo (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2021)
One of the obstacles that occur in the learning process is a misconception, inappropriate understanding of concepts. The misconceptions experienced by each student in one class can be different from one another and are caused by various causes. This study aims to describe the profile of misconceptions experienced by students and the causes of misconceptions in students. This research is descriptive quantitative. The research stage began with the making of a diagnostic test instrument (Four-Tier diagnostic test) which was then validated by a material and education expert. Then, the instrument was tested on grade XII student to collect the data. The data were analyzed descriptively. The target of this research was students of MAN 2 Gresik with a total of 60 students. The results showed the profile of students' misconceptions on Genetic Substance material consisting of the concepts of RNA, DNA, chromosomes, DNA & chromosome gene relationships, protein synthesis, and DNA replication with the category of understanding the concept amounted to 6.1%, 39.9% understand some concepts, 41.8% students experience misconceptions, and 12.2% do not understand concepts. The factors that cause misconceptions consist of students, textbooks, learning media, and teaching methods. Further studies of the development and implementation of digital-based learning media on genetic substance material, should be done near the future to reduce student misconceptions. Keywords: genetic substance, misconceptions, four-tier diagnostic test